2019
DOI: 10.1088/1758-5090/ab30b4
|View full text |Cite
|
Sign up to set email alerts
|

Micropocket hydrogel devices for all-in-one formation, assembly, and analysis of aggregate-based tissues

Abstract: Multicellular aggregated tissues have grown critically important in benchtop biomedical research, both as stand-alone spheroids and when assembled into larger bioengineered constructs. However, typical systems for aggregate formation are limited in their capacity to reliably handle such cultures at various experimental stages in a broadly accessible, consistent, and scalable manner. In this work, we develop a broadly versatile all-in-one biofabrication strategy to form uniform, spherical, multicellular aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…3a, b), which are commonly used to model three-dimensional, diffusionlimited, and high cell-density tissues 35 . A model T47D cell line suspension was mixed with µTAMs, and formed into spheroids by aggregation 36 . As a first demonstration of µTAM stiffness sensing, we measured sensor expansion before and after tissue crosslinking through paraformaldehyde fixation, which we verified would not affect µTAM operation ( Supplementary Fig.…”
Section: Sensor Calibration and Validation In Engineered Tissuesmentioning
confidence: 99%
“…3a, b), which are commonly used to model three-dimensional, diffusionlimited, and high cell-density tissues 35 . A model T47D cell line suspension was mixed with µTAMs, and formed into spheroids by aggregation 36 . As a first demonstration of µTAM stiffness sensing, we measured sensor expansion before and after tissue crosslinking through paraformaldehyde fixation, which we verified would not affect µTAM operation ( Supplementary Fig.…”
Section: Sensor Calibration and Validation In Engineered Tissuesmentioning
confidence: 99%
“…Based on our calibration and modelling experiments, we elected to use the 3% NiPAAM/0.2% bisacrylamide formulation for all described experiments, as it provides greater measurement sensitivity over the stiffness range expected in spheroids 37,38 . A model T47D cell line was mixed with µTAMs, and formed into spheroids by confinement 39 . As a first demonstration of µTAM stiffness sensing, we measured spheroid rigidities before and after tissue crosslinking through paraformaldehyde fixation, which we verified would not affect µTAM operation ( Supplementary Fig.…”
Section: Sensor Calibration and Validation In Engineered Tissuesmentioning
confidence: 99%
“…3C) 41 ; and a micropocket-based system in which cells passively settle into and aggregate in hydrogel cavities ( Fig. 3F; Supplementary Fig S5) 39 . These two techniques both rely on cell-driven aggregation and compaction in confined volumes, and should hence produce reasonably similar structures.…”
Section: Spatial Patterns Of Internal Spheroid Stiffness Depends On Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard, suspension cells culturing within microuidic devices is challenging because simply renewing the medium can lead to accidental cell loss without a trapping mechanism. 18,19 Yue et al reported the fabrication of multi-level channels for cell quantication and cell culture by using a screen printing method. 20 Moreover, microchannels with trapezoidal cross-section have been reported as a retention mechanism that enabled the capture and suspension culture of mammalian cells through inertial microuidics.…”
Section: Introductionmentioning
confidence: 99%